Uma introdução à geometria esférica - Silva, Welder Dan [UNESP] (2015)
One of the main goal of this work, based in some axioms which were chosen such that we could obtain an introduction to the study of Spherical Geometry, is to present the spherical trigonometry. We also present a proof of a formula for the area of a convex and also for non convex polygon on the sphere